Collective Action and Boycott Participation among Young Adults: A Systematic Literature Review - Nugroho, Indra Prapto; Putra, Erdrian Satria (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study is a systematic literature review aimed at analyzing the factors influencing collective action and boycott participation among young adults. A total of 18 selected articles were examined based on their context, methods, theoretical frameworks, variables, and key findings. The results indicate that boycott participation is shaped by a combination of moral, psychological, and social factors, such as ethical values, peer pressure, religiosity, and personality traits. In addition, social media plays a crucial role in facilitating collective mobilization through information dissemination, hashtag activism, and rapid public opinion formation. Theoretically, the reviewed studies predominantly employ the Theory of Planned Behavior, Social Movement Theory, and Political Consumerism perspectives. Findings also show that intention is a key predictor of boycott behavior, although the influence of social and technological factors is often indirect. In conclusion, boycott participation among young adults is a multidimensional phenomenon reflecting the interaction between individual, social, and digital technological factors.